A training pipeline of an arrhythmia classifier for atrial fibrillation detection using Photoplethysmography signal - Kudo, Sota; Chen, Zheng; Zhou, Xue; Izu, Leighton T.; Chen-Izu, Ye; Zhu, Xin; Tamura, Toshiyo; Kanaya, Shigehiko; Huang, Ming (Frontiers in Physiology, 2023)
Plethysmography (PPG) signal is potentially suitable in atrial fibrillation (AF) detection for its convenience in use and similarity in physiological origin to electrocardiogram (ECG). There are a few preceding studies that have shown the possibility of using the peak-to-peak interval of PPG signal (PPIp) in AF detection. However, as a generalized model, the accuracy of an AF detector should be pursued on the one hand; on the other hand, its generalizability should be paid attention to in view of the individual differences in PPG manifestation of even the same arrhythmia, and the existence of sub-types. Moreover, a binary classifier for AF and normal sinus rhythm is not convincing enough for the similarity between AF and ectopic beats. In this study, we project the AF detection as a multiple classes classification and try to propose a training pipeline that is advantageous both to the accuracy and generalizability of the classifier by designing and determining the configurable options of the pipeline, in terms of input format, deep learning model (with hyperparameter optimization), and scheme of transfer-learning. With a rigorous comparison of the possible combinations of the configurable components in the pipeline, we confirmed that 1st order difference of heartbeat sequence as the input format, a 2-layer-CNN--1-layer-Transformer hybrid model as the learning model, and the whole model fine-tuning as the implementing scheme of transfer learning are the best options for the pipeline (F1 value: 0.80, overall accuracy: 0.87).